Representation of the Female Body and Sexuality in the Book Fathul Izar by KH. Abdullah Fauzi: A Study of Andrea Dworkin's Radical Feminism - Muhammad Mugni Ulum; Maman Abdul Djaliel; Rohanda Rohanda (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the representation of women's bodies and sexuality in KH. Abdullah Fauzi's book Fathul Izar through the perspective of Andrea Dworkin's radical feminism. Specifically, this study aims to uncover how the text functions as an instrument of patriarchal control that reduces women to sexual objects and perpetuates a system of subordination in the private sphere. The method used is qualitative with a content analysis design through a critical-interpretive approach. Radical feminist theory was chosen because it views sexuality as an arena of male domination, where women's bodies are defined based on their physical utility. Data were collected through a literature review of the main text of Fathul Izar and related academic literature. The results show that women's bodies are represented subordinately as reproductive objects through the metaphor of "fields" (harts), objects of male sexual pleasure, and biological instruments classified based on physical characteristics or intuition. The discussion reveals the practice of "sacralization of subordination," where prayer rituals and instructions on sexual positions are used to legitimize male control and rob women of their agency. This text positions men as active subjects and women as passive objects deprived of the right to define their own bodily boundaries. This study concludes that Fathul Izar functions as a patriarchal biopolitical instrument that normalizes the total objectification of women. Through a radical reading, this text is deconstructed to encourage a more just and emancipatory reinterpretation of Islamic intellectual heritage for the dignity of women as whole human beings.